The Efficacy of Glasgow Coma Scale (GCS) Score and Acute Physiology and Chronic Health Evaluation (APACHE) II for Predicting Hospital Mortality of ICU Patients with Acute Traumatic Brain Injury - Amir Nik (Bulletin of Emergency and Trauma, 2018)
Objective: To compare the efficacy and functional outcome of Glasgow Coma Scale (GCS) score with that of Acute Physiology and Chronic Health Evaluation Score II (APACHE II) in patients with multiple trauma admitted to the ICU.Methods: This cross-sectional study included 125 patients with traumatic brain injury associated with systemic trauma admitted to the ICU of Shahid Kamyab Hospital, Mashhad, between September 2015 and December 2016. On the day of admission, data were collected from each patient to calculate GCS and APACHE II scores. Sensitivity, specificity, and correct outcome prediction was compared between GCS and APACHE II.Results: Positive predictive value (PPV) at the cut-off points was higher in APACHE II (80.6%) compared with GCS (69.2%). However, negative predictive value (NPV) of GCS was slightly higher in comparison with APACHE II. Moreover, the area under the receiver operating characteristic (ROC) curve for sensitivity and specificity of GCS and APACHE II showed no significant difference (0.81±0.04 vs. 0.83±0.04; p=0.278 respectively).Conclusion: Our study suggested that there was no considerable difference between GCS and APACHE II scores for predicting mortality in head injury patients. Both scales showed acceptable PPV, while APACHE II showed better results. However, the utilization of GCS in the initial assessment is recommended over APACHE II as the former provides higher time- and cost-efficiency.